f(x)=x- and g(x)=x(second power) -x
(f+g)(-3)=? (simplify answer)
Thank you for the opportunity to help you with your question!
To begin, (f+g)(-3) = f(-3)+g(-3).
Now, f(-3) = -(-3) = 3 and g(-3) = (-3)^2 * - (-3)= 9+3 = 12.
This brings us to f(-3)+g(-3) = 3+12 = 15.
Are you available I have some questions for you
Howicj would you charge to do a homework assignment and quiz 40 questions a piece by today or tomorrow?
Hey sorry I just saw this. And how would I charge? Or are you asking what to charge on this webstite? What kind of quiz and homework assignment?
Because personally I think it would be fair for $1 a question, so $40 for 40 homework questions and maybe $20 for a quiz. But again, it would also depend on what type of problems.
Content will be erased after question is completed.
Enter the email address associated with your account, and we will email you a link to reset your password.
Forgot your password?